2018–2019 Florida Citrus Production Guide: Blight - Ozgur Batuman; Pamela D. Roberts; Ronald H. Brlansky (EDIS, 2018)
Citrus blight is a wilt and decline disease of citrus whose cause has not been determined. The first symptoms are usually a mild wilt and grayish cast to the foliage often accompanied by zinc deficiency symptoms on trees. Trees rapidly decline with extensive twig dieback, off-season flowering, and small fruit. Blight trees reach a stage of chronic decline, but seldom die. This 2-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by Ozgur Batuman, Pamela D. Roberts, and Ronald H. Brlansky, and published by the UF/IFAS Plant Pathology Department, May 2018.